Long-term efficacy and safety profile of multiple injections of intravitreal dexamethasone implant to manage diabetic macular edema: A systematic review of real-world studies - Claudio Bucolo; Lucia Gozzo; Laura Longo; Silvana Mansueto; Daniela Cristina Vitale; Filippo Drago (Elsevier, 2018)
Introduction: Systematic review of real-world studies about repeated dexamethasone intravitreal implant (DEXi) 0.7 mg in diabetic macular edema management, in order to identify the effective window of time occurring between injections, the critical evaluation of efficacy of the treatment, and the relative long-term safety in the real life setting. Methods: Literature databases such as PubMed, SCOPUS, and EMBASE were used to identify reports including DEX implant injections. Results: Twenty-one peer-reviewed publications were identified. DEX implants retreatment was considered on a pro re nata (PRN) basis at any time or starting from month three or four. About 1/3 of the eyes were retreated before six months from first injection (range 0-86.7%). Mean retreatment average time was 5.3 ± 0.9 months, with an estimated average of 1.3 injections each six months. There was no statistical correlation between average retreatment time and incidence of adverse events or other variables investigated. Limited safety issues related to implants number have been found, suggesting an overall good tolerance of long-term DEXi. Conclusions: Comprehensive evaluation of real-world data suggests an average DEXi duration close to five months, following a PRN treatment strategy, including about 1/3 of patients. Repeated DEXi administration revealed an acceptable long-term efficacy/safety ratio. Keywords: Diabetic macular edema, Dexamethasone, Intravitreal implant, Systematic review, Ocular drug delivery